The Quest for Neurodegenerative Disease Treatment—Focusing on Alzheimer’s Disease Personalised Diets - Matei Palimariciuc; Ioana-Miruna Balmus; Bogdan Gireadă; Alin Ciobica; Roxana Chiriță; Alin-Constantin Iordache; Mihai Apostu; Romeo Petru Dobrin (Current Issues in Molecular Biology, 2023)
Dementia represents a clinical syndrome characterised by progressive decline in memory, language, visuospatial and executive function, personality, and behaviour, causing loss of abilities to perform instrumental or essential activities of daily living. The most common cause of dementia is Alzheimer’s disease (AD), which accounts for up to 80% of all dementia cases. Despite that extensive studies regarding the etiology and risk factors have been performed in recent decades, and how the current knowledge about AD pathophysiology significantly improved with the recent advances in science and technology, little is still known about its treatment options. In this controverted context, a nutritional approach could be a promising way to formulate improved AD management strategies and to further analyse possible treatment strategy options based on personalised diets, as Nutritional Psychiatry is currently gaining relevance in neuropsychiatric disease treatment. Based on the current knowledge of AD pathophysiology, as well as based on the repeatedly documented anti-inflammatory and antioxidant potential of different functional foods, we aimed to find, describe, and correlate several dietary compounds that could be useful in formulating a nutritional approach in AD management. We performed a screening for relevant studies on the main scientific databases using keywords such as “Alzheimer’s disease”, “dementia”, “treatment”, “medication”, “treatment alternatives”, “vitamin E”, “nutrition”, “selenium”, “Ginkgo biloba”, “antioxidants”, “medicinal plants”, and “traditional medicine” in combinations. Results: nutrients could be a key component in the physiologic and anatomic development of the brain. Several nutrients have been studied in the pursuit of the mechanism triggered by the pathology of AD: vitamin D, fatty acids, selenium, as well as neuroprotective plant extracts (i.e., Ginkgo biloba, Panax ginseng, Curcuma longa), suggesting that the nutritional patterns could modulate the cognitive status and provide neuroprotection. The multifactorial origin of AD development and progression could suggest that nutrition could greatly contribute to the complex pathological picture. The identification of adequate nutritional interventions and the not yet fully understood nutrient activity in AD could be the next steps in finding several innovative treatment options for neurodegenerative disorders.